Management of Autism in the Adult Intensive Care Unit. (January 2014) - Hsieh, Emily; Oh, Scott S.; Chellappa, Parkavi; Szeftel, Roxy; Jones, Heather D.
Autism comprises a growing segment of the population and can be a management challenge in the intensive care unit (ICU). We present the case of a 22-year-old male with severe autism and intellectual disorder who developed respiratory failure and required a prolonged ICU course. This patient exhibited severe distress, aggression, and self-injurious behavior. Management challenges included sedation, weaning from sedation, and liberation from mechanical ventilation. Success was achieved with a multispecialty team and by tailoring the environment and interactions to the patient's known preferences. The use of dexmedetomidine to wean high-dose benzodiazepines and opiates also permitted successful liberation from mechanical ventilation.